TECHNICAL SPECIFICATIONS OF COLOSSNIC GLASSES IN CLEANING FROM SMALL POLLUTION - Yangiboyev Ikromjon Berdikul o‘g‘li; Shodiyev Dilmurod Turdimuratovich; Berdanov Erkin Xamrakulovich (Journal Park Publishing, 2026)
The article presents the results of studies of the influence of the distance between different grates on the efficiency of cleaning equipment. It is known that during the cleaning process, the distance between the grates of the grate affects the cleaning efficiency of the equipment.
Keywords: Cotton, cotton fiber, cleaner, feeder, peg drum, mesh surface, temperature, humidity, clogging.